Does magnification of SEM image influence quantification of particulate matters deposited on vegetation foliage. (December 2018) - Lin, Lin; Yan, Jingli; Chen, Guojian; Tang, Rongli; Bao, Le; Ma, Keming; Zhou, Weiqi; Yuan, Xiu; Yin, Zhe; Zhou, Shuwen
Highlights: Ultrafine and fine particles are more sensitive to magnification than big particles. The percentage of leaf area covered of particles is a relatively stable index. Magnifications 1000× and 2000× are more comparable than other magnifications. Abstract: The metrics used to quantify the particles on the leaf surface can serve as indicators for the quality of the atmospheric environment and is employed to evaluate the ecosystem services that plants can provide. Magnification of an SEM image may affect the recognition of particles in various aspects, yet little research has examined the impact. In this study, images were obtained at magnifications of 500×, 1000×, 2000×, and 5000× for a widely planted vegetation fence species in Beijing: Euonymus japonicas . Particle amount per leaf area increased as magnification increased; the percentage of the leaf area covered by particles was a relatively stable index across magnifications at around 7% except for the magnification 2000× which was around 15%; and the weight of particles per leaf area was unstable over all magnifications. The mean area of each particle decreased from 5.68 μm 2 at magnification 500× to 0.20 at magnification 5000×, and shape complexity increased as magnification increased from 1.29 at magnification 500× to 1.50 at magnification 5000×. Particles with a diameter of less than 2.5 μm are more sensitive to scale than particles with a diameter greater than 2.5 μm of judged by the differences of the characteristics, diameter, area and shape index, of particles with different diameter ranges over four magnifications. Regarding the percentage characteristic, the percentage of particles with a diameter smaller than 1 μm increased as the magnification increased and accounted for 46% at magnification 500× and 96% at magnification 5000×. The percentage of particles with an area smaller than 1 μm 2 also increased as the magnification increased accounting for 56% at magnification 500× and 99% at magnification 5000×. Particles with shape index between 1–1.5 accounted for most of the particles across all four magnifications of which the percentage was 0.66–0.80. Therefore, when comparing the results from different magnifications, three factors should be considered carefully: magnification, quantification index, and particle size range. The revealed relationship of the factors can facilitate the understanding of the metrics as indicators for atmospheric environments and vegetation as a sink for atmospheric particles to improve the urban environment.